Towards interprofessional networking in medication management of the aged: current challenges and potential solutions in Finland - Sonja Kallio; Anne Kumpusalo-Vauhkonen; Timo Järvensivu; Antti Mäntylä; Marika Pohjanoksa-Mäntylä; Marja Airaksinen (Taylor & Francis Group, 2016)
Objective: The Finnish Medicines Agency (Fimea) initiated a programme in 2012 for enhancing interprofessional networking in the medication management of the aged. The goal is to develop national guidelines for interprofessional collaboration with respect to medication management. This study aims to explore the challenges and potential solutions experienced by existing health care teams in managing medication of the aged: (1) at the individual and team level (micro level), (2) organisational level (meso level) and (3) structural level (macro level). Design: Group discussions (n = 10), pair (n = 3) and individual interviews (n = 2). Abductive content analysis combining data and theory was applied. Networking was used as a theoretical framework. Setting: Meetings (n = 15) organised by Fimea in the formation phase of the interprofessional network in 2012. Subjects: Health care professionals (n = 55). Main outcome measures: Challenges and solutions in the medication management of the aged at the micro, meso and macro levels. Results: Challenges in interprofessional collaboration, problems with patient record systems, and the organisation of work and lack of resources were present at all the levels contributing to patients' medication problems. Participants suggested multiple potential solutions to improve interprofessional collaboration, sharing of tasks and responsibilities, better exploitation of pharmaceutical knowledge and developing tools as being the most commonly mentioned. Conclusions: Optimising medication use of the aged requires new systemic solutions within and between different system levels. The main challenges can be solved by clarifying responsibilities, enhancing communication and applying operational models that involve pharmacists and the use of information technology in medication management.KEY POINTS An interprofessional team approach has been suggested as a solution to promote rational medicine use among the aged. Fragmented health care system and lack of coordinated patient care are reasons for medication related problems of the aged. Challenges in the implementation of interprofessional collaboration in medication management appear in legislation, information systems, operational models and individuals' attitudes. Optimising medications requires better interprofessional networking and new systemic solutions within and between macro, meso and micro levels.